ATTENUATION OF CIGARETTE-SMOKE-INDUCED OXIDATIVE STRESS BY OAT DIET - Soetedjo, Farida Anggraini; Kristijanto, Johanes Aprilius Falerio; Khamidah, Nur (Indonesian Journal for Health Sciences, 2024)
Even after cessation of cigarette smoke exposure, long-term exposure leads to lung fibrous tissue growth characteristically by oxidative stress. Oat, an inexpensive dietary source with antioxidant characteristics, is expected to alleviate oxidative stress in the lung tissue after exposure to cigarette smoke has ceased. This research aims to evaluate the effect of an oat diet in alleviating oxidative stress in the lung tissue of BALB/c mice after cessation of cigarette smoke exposure. A randomized post-test-only control group design was used for this research. The sample used in this experiment is male BALB/c mice (n = 33). Mice with BALB/c strain were separated into two groups: (1) control and (2) treatment. SOD, GSH, and MDA were the variables of the study. Cigarette smoke exposure decreases the activity of SOD and GSH and increases the concentration of MDA. After cigarette smoke exposure had been stopped in the oat-treated mice group, SOD and GSH activities were enhanced, and the MDA content dropped. This research's variable outcomes were statistically significant (P0.05) from the standard feed alone-treated BALB/c mice group. Thus, consuming oats may alleviate oxidative stress implicated in lung fibrogenesis following cessation of tobacco smoke exposure